Strategies for coping with and adapting to climate change: Evidence from agricultural households in Bangladesh - Rakib, Muntaha (International Food Policy Research Institute, 2014)
This policy note summarizes research that explored the perceptions of agricultural households in rural Bangladesh about climate change and their choices of coping mechanisms and adaptation strategies.